The Use Of Slang Amongst Undergraduate Students Of A Malaysian Public University (JOURNAL OF ADVANCES IN LINGUISTICS, 2014)
Slang is the use of highly informal words and expressions that are not considered standard in the speaker's dialect or language. Slang is very often colloquial: the language and dialect tend to be specific to a particular territory. Slang is a central part of young generation's experience, but contrary to many adults perception of slang as more or less uniform youth language The social meaning of slang is as variable as the teenagers who use it. In short, slang is an integral part of teenage communication. It gives them an identity of youth style of expression. Though slangs are language and culture specific, but they are often transmitted from one culture and language to another. Recent electronic communications contribute a lot in this process. The aim of this study was to show that if Malaysian youth use English slang in their language. The two major objectives were: 1. to illustrate if Malaysian youth are familiar with slang. 2. To examine what kind of slang they use more in compare with other kinds of slang. A pilot-test consists of 20 slang items was administered to 60 students. The respondents were in final semester of bachelor of English language at UPM.Â  The data obtained from the study was coded and analyzed using the statistical package for social sciences (spss). The analyzing of data showed that the internet slang, abbreviations slang, and movie slang are used frequently by youth generation. It seems that they are familiar with these sorts of slang. The reasons can be because of using internet a lot nowadays, another reason can be media, which has the most important role in this case.